Selection of Reference Genes for Normalization of Gene Expression Data in Blood of Machado-Joseph Disease/Spinocerebellar Ataxia Type 3 (MJD/SCA3) Subjects - Ferreira, Ana F.; Raposo, Mafalda; Vasconcelos, João; Costa, Maria do Carmo; Lima, Manuela (Journal of molecular neuroscience, 2019)
Alongside with the emergent clinical trials for Machado-Joseph disease/Spinocerebellar ataxia type 3 (MJD/SCA3) comes the need to identify molecular biomarkers of disease that can be tracked throughout the trial. MJD is an autosomal dominant neurodegenerative disorder caused by expansion of a CAG repeat in the coding region of the ATXN3 gene. Previous findings indicate the potential of transcriptional alterations in blood of MJD patients as biomarkers of disease. Accurate quantification of gene expression levels by quantitative real-time PCR (qPCR) depends on data normalization, usually performed using reference genes. Because the expression level of routinely used housekeeping genes may vary in multiple biological and experimental conditions, reference gene controls should be validated in each specific experimental design. Here, we aimed to evaluate the expression behavior of five housekeeping genes previously reported as stably expressed in peripheral blood of patients from several disorders—peptidylprolyl isomerase B ( PPIB ), TNF receptor associated protein 1 ( TRAP1 ), beta-2-microglobulin ( B2M ), 2,4-dienoyl-CoA reductase 1 ( DECR1 ), and folylpolyglutamate synthase ( FPGS ). Expression levels of these five genes were assessed by qPCR in blood from MJD subjects (preataxic and patients) and matched controls. While all housekeeping genes, here studied, were stably expressed in our sets of samples, TRAP1 showed to be the most stable gene by NormFinder and BestKeeper. We, therefore, conclude that any of these genes could be used as reference gene in future qPCR studies using blood samples from MJD subjects.